Morphological Alteration Caused by Brassinosteroid Insensitivity Increases the Biomass and Grain Production of Rice - Morinaka, Yoichi (American Society of Plant Biologists, 2006)
The rice (Oryza sativa) dwarf mutant d61 phenotype is caused by loss of function of a rice BRASSINOSTEROID INSENSITIVE1 ortholog, OsBRI1. We have identified nine d61 alleles, the weakest of which, d61-7, confers agronomically important traits such as semidwarf stature and erect leaves. Because erect-leaf habit is considered to increase light capture for photosynthesis, we compared the biomass and grain production of wild-type and d61-7 rice. The biomass of wild type was 38% higher than that of d61-7 at harvest under conventional planting density because of the dwarfism of d61-7. However, the biomass of d61-7 was 35% higher than that of wild type at high planting density. The grain yield of wild type reached a maximum at middensity, but the yield of d61-7 continued to increase with planting density. These results indicate that d61-7 produces biomass more effectively than wild type, and consequently more effectively assimilates the biomass in reproductive organ development at high planting density. However, the small grain size of d61-7 counters any increase in grain yield, leading to the same grain yield as that of wild type even at high density. We therefore produced transgenic rice with partial suppression of endogenous OsBRI1 expression to obtain the erect-leaf phenotype without grain changes. The estimated grain yield of these transformants was about 30% higher than that of wild type at high density. These results demonstrate the feasibility of generating erect-leaf plants by modifying the expression of the brassinosteroid receptor gene in transgenic rice plants.